2003
DOI: 10.1016/s1535-6108(03)00051-5
|View full text |Cite
|
Sign up to set email alerts
|

MOZ-TIF2-induced acute myeloid leukemia requires the MOZ nucleosome binding motif and TIF2-mediated recruitment of CBP

Abstract: The MOZ-TIF2 fusion is associated with acute myeloid leukemia (AML) with inv(8)(p11q13). MOZ is a MYST family histone acetyltransferase (HAT), whereas TIF2 is a nuclear receptor coactivator that associates with CREB binding protein (CBP). Here we demonstrate that MOZ-TIF2 has transforming properties in vitro and causes AML in a murine bone marrow transplant assay. The C2HC nucleosome recognition motif of MOZ is essential for transformation, whereas MOZ HAT activity is dispensable. However, MOZ-TIF2 interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
177
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(191 citation statements)
references
References 48 publications
7
177
1
2
Order By: Relevance
“…The CBP/p300-interacting domain (CID) of TIF2 remains intact in MOZ-TIF2 resulting from inv(8)(p11;q13), suggesting that this fusion protein acts through p300 and CBP and that aberrant acetylation plays a role in leukemogenesis (Figure 3b). MOZ-TIF2 displays intrinsic transforming ability in vitro and induces AML in murine bone marrow transplant assays (Deguchi et al, 2003). In support of the involvement of p300 and CBP, the CID of TIF2 is crucial for these activities.…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 95%
“…The CBP/p300-interacting domain (CID) of TIF2 remains intact in MOZ-TIF2 resulting from inv(8)(p11;q13), suggesting that this fusion protein acts through p300 and CBP and that aberrant acetylation plays a role in leukemogenesis (Figure 3b). MOZ-TIF2 displays intrinsic transforming ability in vitro and induces AML in murine bone marrow transplant assays (Deguchi et al, 2003). In support of the involvement of p300 and CBP, the CID of TIF2 is crucial for these activities.…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 95%
“…Thus, the fusion protein induces properties typical of leukaemic stem cells. Interestingly, the intrinsic HAT activity of MOZ is required for neither self-renewal nor leukaemic transformation, but its nucleosome-binding motif is essential for both [103,104]. Importantly, the CBP interaction domain within TIF2 is also essential for both processes [103,104].…”
Section: Histone Modifications and Cancermentioning
confidence: 99%
“…Recent biochemical purifications revealed that both the Drosophila and mammalian MOF proteins reside in multi-protein complexes and that most of these interacting proteins are conserved between Drosophila and mammals (Table 2; Dou et al, 2005;Smith et al, 2005;Mendjan et al, 2006). Co-purification of four human MSL proteins (hMSL1, hMSL2, hMSL3 and hMOF) showed that the MSL (Borrow et al, 1996;Carapeti et al, 1998;Champagne et al, 1999Champagne et al, , 2001Chaffanet et al, 2000;Kitabayashi et al, 2001;Pelletier et al, 2002;Bristow and Shore, 2003;Deguchi et al, 2003;Kindle et al, 2005;Katsumoto et al, 2006;Thomas et al, 2006;Ohta et al, 2007 Abbreviation: HAT, histone acetyltransferases.…”
Section: The Histone Acetyltransferase Mofmentioning
confidence: 99%